In Vitro Preliminary Characterization of Lactiplantibacillus plantarum BG112 for Use as a Starter Culture for Industrial Dry-Fermented Meats - María Inés Palacio; María Julia Ruiz; María Fernanda Vega; Analía Inés Etcheverría (Fermentation, 2025)
The objective of this study was to perform a preliminary in vitro characterization of Lactiplantibacillus plantarum BG112, assessing its safety and technological features for potential application as a culture starter for an industrial fermented dry meat product. In vitro assays assessed its viability, probiotic properties, and safety for use in food formulations. The strain was characterized through morphological and biochemical tests, carbohydrate fermentation profiling, and various in vitro assays based on FAO/WHO criteria for probiotic selection. These included proteolytic activity, auto-aggregation capacity, tolerance to simulated gastric juice and bile salts, antimicrobial activity, and resistance to sodium chloride, nitrite, and low pH. Safety evaluations were also performed by testing antibiotic susceptibility, hemolytic activity, and DNAse production. The results showed that L. plantarum BG112 exhibited strong tolerance to adverse environmental conditions typically found during sausage fermentation and ripening, along with significant inhibitory activity against pathogenic bacteria, such as Escherichia coli O157:H7, Salmonella Typhimurium, and Staphylococcus aureus. The strain also demonstrated no hemolytic or DNAse activity and presented a favorable antibiotic sensitivity profile, meeting key safety requirements for probiotic use. Further studies using meat matrices and in vivo models are needed to validate these findings. This study contributes to the early-stage selection of safe and technologically suitable strains for use in fermented meat products. These findings support the potential application of L. plantarum BG112 as a safe and effective starter culture in the development of high-value, premium fermented meat products, aligned with current consumer demand for health-enhancing and natural foods.